THE INFLUENCE OF VIDEO MEDIA ON THE PREPARAEDNESS IN FACING FLOOD DISASTERS IN ELEMENTARY SCHOOL IN BENGKULU CITY - Ida Rahmawati; Vike Pebri Giena; Neni Triana; Buyung Keraman; Nur Haadiy (Nurse and Health: Jurnal Keperawatan, 2020)
BackgroundFlood disasters can cause material losses and fatalities, especially in the city of Bengkulu. Disaster preparedness is needed from an early age in order to reduce the impact of disaster risk. Elementary school students are still had lack of knowledge about preparedness in dealing with floods, in general. Bengkulu Elementary School (SDN) 103 is one of the schools affected by flooding when the River Basin (DAS) is unable to accommodate river water discharge.ObjectiveThe purpose of this study was to determine the effect of video media on student preparedness in dealing with floods in Bengkulu City.MethodsThe study design used a Pre Experiment with One Group Pretest-Posttest design. The population in this study were all fifth grade children in SDN 103 Bengkulu City. The total sampling technique was used in this study. The data were collected by using primary data taken from the results of a questionnaire filled out by respondents. T-test was used as statistical test.ResultThe results of the study were obtained (1) from 27 students before being given video media, namely 14 students in the very ready category (51.9%) and 13 students in the ready category (48.1%); (2) after being given video media, there were 20 (74.1%) category students were very prepared and 7 students were prepared categories (25.9%) (3) Paired sample t-test analysis showed p-value of 0.008 <0.05. There is influence of video media on preparedness in facing flood disaster at SDN 103 Bengkulu City in 2019.ConclusionThe importance of early education about disaster is expected to reduce the impact of disasters, especially flood disasters in risk areas. It is expected that schools will be able to include curriculum and training for their students on disaster preparedness training.